TÜRK TARİHİNDE MİLLİ HÂKİMİYET FİKİRİNİN ORTAYA ÇIKIŞI VE TARİHİ HAKİMİYET - Maden, Fahri (Gazi Türkiyat Türklük Bilimi Araştırmaları Dergisi, Sayı 7, Ankara 2010, s.301-326., 2010)
Türk Tarihinde Milli Hâkimiyet fikrinin ortaya çıktı ve geliş imi çeş itli a şamalardan geçmiş tir. Osmanlı Devleti’nin son yıllarında Türk aydınının zihninde yer almaya baş layan “hâkimiyet-i milliye” fikri, Osmanlı Devleti’nin yıkılıp yerine milli bir devlet olarak kurulan Türkiye Cumhuriyeti’nin temel ilkelerinden biri olarak kabul görmüş ve olgunlaş mış tır. Milli Hâkimiyet fikrinin geli şmesinde II. Meş rutiyet dönemi önemli bir kilometre taş ıdır. Ancak bu fikir uygulama alanında yer almak için Atatürk faktörüne ihtiyaç duymuş tur. Zira Türk siyasi hayatında milli hâkimiyet ilkesini cesaretle ele alan ve savunan Atatürk olmuş tur. Atatürk’ün tesis ettiğ i cumhuriyet rejimi sayesinde yönetimde milli hâkimiyet esasına geçmek mümkün olabilmiş tir. Coming out the idea of national sovereignity and its improvement have had variety of stages in Turkish history at the last years of Ottoman Empire. Beginning to make on impression on the mind of Turkish ntellectual, the idea of “Sovereignity of National” had recovered and been admited as one of the main Fundamentals of Turkish Republic that been established as a new government instead of demoslished Ottoman Empire. The Second Constitutional Monarchy is an important factor on the improvement of the idea of national sovereignity. However, the idea had needed Atatürk to take a place in the implementation area. He was Atatürk dealing with a courage way and defensing the fundamental of national sovereignity in Turkish political life. It could bu possible to pass the princible of national sovereignity in the administration thanks to the regime of republic that Atatürk founded.
Coming Out and Historical Improvement the Idea of Soveregnity in Turkish History
Keywords: Milli Hâkimiyet, Milli rade, II. Me rutiyet, Anayasa